Techno Commercial Analysis of Liquefied Petroleum Gas Recovery From Natural Gas Using Aspen HYSYS - Ali, Usman; Zafar, Muhammad; Ahmed, Ashfaq; Zaman, Hafiz Kamran; Razzaq, Abdul; Daood, Syed Sheraz; Bashir, Muhammad; Park, Young-Kwon (Frontiers in Energy Research, 2021)
Liquefied petroleum gas is an alternative, relatively clean and supreme source of energy, is being used as a key component in the global energy supply. The international trade agreements and chemical, non-chemical demand of liquefied petroleum gas with the increase in the world’s population has brought its production from the processing of natural gas to the limelight. During its processing, a variety of different components are extracted from it, including methane and ethane which remains in the bulk as natural gas. The objective of this research work is to find the capability of investigating the liquefied petroleum gas recovery performance to make the process economical by saving the processing cost and energy. The novelty of this work is to deal with the design and simulation of liquefied petroleum gas plant using Aspen HYSYS. To make this process energy efficient and economical, different schemes of process alternatives were applied by reducing the sizes of exchanger and other equipment. Three cases are studied in which feed is pre-cooled by rerouting the stream and/or by repositioning of the chiller for the recovery of liquefied petroleum gas from natural gas by analyzing their cost and process parameters. The outcome of this investigation is to present plenty of suggestions to improve the process efficiency and minimize the requirement to over design the plant components.